St Regulus Tower, St Andrews - Where did the Stones with which it was built come from? (Proceedings of the Society of Antiquaries of Scotland, 1913)
The stone used to build the tower differs from that used for the cathedral and has survived in better condition. It is concluded, on the basis of microscopic analysis that the stone used in the building of St Regulus Tower was local and not from Northumberland as has been argued elsewhere.